Retrograde tibial intramedullary nail versus minimally invasive locking plate for extra-articular distal tibial fractures: a comparative and retrospective study - Hui Liu; Weizhen Xu; Yuanfei Xiong; Jinhui Zhang; Zunying Xu; Jin Wu (Journal of Orthopaedic Surgery and Research, 2024)
Abstract Background Distal tibial fractures represent common lower limb injuries, frequently accompanied by significant soft tissue damage. The optimal surgical approach for managing these fractures remains a topic of considerable debate. The aim of this study was to perform a comparative analysis of the outcomes associated with retrograde intramedullary tibial nails (RTN) and minimally invasive plate osteosynthesis (MIPO) in the context of treating extra-articular distal tibial fractures. Methods A retrospective review was conducted on a cohort of 48 patients who sustained extra-articular distal tibial fractures between December 2019 and December 2021. Patients underwent either RTN or MIPO procedures. Various parameters, including operative duration, intraoperative fluoroscopy exposure, time to union, duration until full weight-bearing, American Orthopedic Foot and Ankle Society (AOFAS) scores, and complications, were recorded and compared between the two treatment groups. Results No statistically significant differences were observed in operative duration, time to union, angulation of the distal tibial coronal plane, or AOFAS scores between the RTN and MIPO groups. However, the RTN group had a higher average number of intraoperative fluoroscopy images (8.2 ± 2.3) compared to the MIPO group (4.1 ± 2.0). The RTN group demonstrated shorter average hospital stays (7.1 ± 1.4 days) and a quicker return to full weight-bearing (9.9 ± 1.3 weeks), which were significantly superior to the MIPO group (9.0 ± 2.0 days and 11.5 ± 1.5 weeks, respectively). In terms of complications, the RTN group had one case of superficial infection, whereas the MIPO group exhibited two cases of delayed union and nonunion, two occurrences of deep infection, and an additional three cases of superficial infection. Conclusions Both RTN and MIPO are effective treatment options for extra-articular distal tibial fractures. However, RTN may offer superior outcomes in terms of decreased inpatient needs, faster return to full weight-bearing capacity, and a lower rate of complications.